2015
DOI: 10.1113/jp271716
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of 5‐HT1A receptor‐mediated transmission in dorsal raphe serotonin neurons

Abstract: Key pointsr In the dorsal raphe nucleus, it is known that serotonin release activates metabotropic 5-HT 1A autoreceptors located on serotonin neurons that leads to an inhibition of firing through the activation of G-protein-coupled inwardly rectifying potassium channels.r We found that in mouse brain slices evoked serotonin release produced a 5-HT 1A receptor-mediated inhibitory postsynaptic current (IPSC) that resulted in only a transient pause in firing.r While spillover activation of receptors contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 67 publications
1
40
0
Order By: Relevance
“…Indeed, 5-HT receptors inhibit I Ca in neurons (Bayliss et al, 1997b; Foehring, 1996; Penington and Kelly, 1990) and several GPCRs use this mechanism in adrenal chromaffin cells, including P2Y purinergic, μ-opioid, prostaglandin EP3, and alpha adrenergic receptors (Albillos et al, 1996; Brede et al, 2003; Carabelli et al, 1998; Currie and Fox, 1996; Jewell et al, 2011). However, we found the 5-HT 1A receptor had no effect on I Ca in chromaffin cells (figure 6), and also had no effect on GIRK channels (figure 6) which help control membrane excitability in the CNS (Courtney and Ford, 2016; Luscher et al, 1997; Penington et al, 1993). Using fluorescent Ca 2+ imaging we confirmed that Ca 2+ entry was unaltered and intracellular Ca 2+ handling (clearance, release from intracellular stores, etc.)…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, 5-HT receptors inhibit I Ca in neurons (Bayliss et al, 1997b; Foehring, 1996; Penington and Kelly, 1990) and several GPCRs use this mechanism in adrenal chromaffin cells, including P2Y purinergic, μ-opioid, prostaglandin EP3, and alpha adrenergic receptors (Albillos et al, 1996; Brede et al, 2003; Carabelli et al, 1998; Currie and Fox, 1996; Jewell et al, 2011). However, we found the 5-HT 1A receptor had no effect on I Ca in chromaffin cells (figure 6), and also had no effect on GIRK channels (figure 6) which help control membrane excitability in the CNS (Courtney and Ford, 2016; Luscher et al, 1997; Penington et al, 1993). Using fluorescent Ca 2+ imaging we confirmed that Ca 2+ entry was unaltered and intracellular Ca 2+ handling (clearance, release from intracellular stores, etc.)…”
Section: Discussionmentioning
confidence: 85%
“…Additional future studies could include pharmacological investigation of potential receptors (GR, glutamate, GABA) responsible for the effect of chronic CORT on intrinsic excitability and also how the DR neurons respond to bath application of 5‐HT or a 5‐HT 1A agonist following chronic CORT administration. The latter experiment would provide insight into the effect of glucocorticoid excess on the autoregulation of these target‐specific populations and represents an area of particular interest because most antidepressant medications are thought to achieve therapeutic efficacy through accumulation of 5‐HT within the DR and desensitization of somatodendritic 5‐HT 1A inhibitory autoreceptors on serotonergic projection neurons (Artigas, ; Courtney & Ford, ).…”
Section: Resultsmentioning
confidence: 99%
“…SSRI antidepressants, which have a more limited effect on 5-HT release from dendrites than from the soma and terminals, markedly increase extracellular 5-HT in DRN that involves both somatic and dendritic release [45]. The 5-HT released within DRN induces feedback inhibition of 5-HT neuron firing activity by stimulation of somatodendritic 5-HT 1A -negative autoreceptors, which results from local release rather than extended diffusion of 5-HT throughout the extracellular space [46]. We found that the hypothermic response to 8-OHDPAT, known to be mediated by 5-HT 1A autoreceptors but not heteroreceptors in mice [35], is attenuated by pretreatment with the 5-HT 2B receptor agonist BW723C86.…”
Section: Serotonergic Tone Results From An Opposite Control Exerted Bmentioning
confidence: 99%